UHPLC quantitation method for new thiazolidinedione LPSF/GQ-02 and in vitro/in vivo kinetic studies - Vieira, Carla Monalizi [UNESP]; de Campos, Michel Leandro [UNESP]; Padilha, Elias Carvalho [UNESP]; Pitta, Marina; Pitta, Ivan da Rocha; Alves de Lima, Maria do Carmo; Peccinini, Rosângela Gonçalves [UNESP] (Bentham Science Publishers, 2016)
Background: LPSF/GQ-02 is a promising benzylidene thiazolidinedione that has demonstrated antidiabetic,antidyslipidemic,anti-atherosclerotic properties and can also treat non-alcoholic fatty liver disease. Despite all activity studies of the new compound,its pharmacokinetics are not yet described. Objective: The aim of this study was to perform its first pharmacokinetic profile. Methods: For this purpose a bioanalytical method for the quantitation of 5-(4-Chloro-benzylidene)-3-(4-methylbenzyl)-thiazolidine-2,4-dione (LPSF/GQ-02) was developed and validated. A Waters UPLC chromatographer using a BEH column (2.1×50mm,1.7µm particle),mobile phase water:acetonitrile (20:80) was used. The range of calibration curve in plasma was 1.9 to 250 ng/mL with r = 0.9997. LPSF/GQ-02 stability was evaluated in rat plasma and buffers at pH 1.2 and 7.4. The pharmacokinetic assay was carried out in male Wistar rats weighing 250-300 g. The animals received LPSF/GQ-02 at 3 mg/kg by intravenous route. The animals were used to perform a preliminary safety study concerning the evaluation of liver and kidney biomarkers (ALT,AST,urea,creatinine). Results: The obtained pharmacokinetic parameters were elimination half-life of 4.44 h,Cl of 8.00 L/h.kg,Vd of 45.60 L/kg and MRT of 3.79h. No difference was observed for the liver and kidney biomarkers. Conclusion: The intravenous pharmacokinetic parameters are in agreement with a good future posology,even though the plasma concentrations from oral administration were not quantifiable in a dose of 12 mg/kg. The preliminary safety study demonstrated no acute effect of the drug in liver and kidneys. The LPSF/GQ-02 is a new thiazolidinedione that should continue being evaluated for future clinical use.
Keywords: Bioanalytical method; LPSF/GQ-02; Preclinical pharmacokinetics; Safety assessment; Thiazolidinedione; UHPLC